Expert system for early diagnosis of eye diseases infecting the Malaysian population - Ibrahim, F.; Basheer Ali, J.; Jaais, F.; Nasir Taib, M. (2001)
This paper describes a knowledge based system employing certain expert system rules to detect different kind of eye diseases found in Malaysia. The types of eye diseases that can be detected with this system are allergic or infectious conjunctivitis, secondary and senile cataract, open angle glaucoma and acute glaucoma, keratitis and dry eyes syndrome. These are the most frequent eye diseases infecting the Malaysian population. The project was designed and programmed via the object-oriented expert system shell software, EXSYS. Expert rules were developed based on the symptoms of each type of the eye diseases, and they were presented using a tree graph forward chaining with depth search first method. In order to enhance user interaction with the system, graphical user interfaces were employed. Previously, several similar works have been published, but they are limited to detecting a single disease and also required expert medical officer to operate. The expert system described in this paper is able to detect and gives early diagnosis of five types of eye diseases; inclusive of senile, secondary, open angle, acute, allergic and infections.